Evaluation of color vision in a waxy foundry plant - Kh Sadeghniiat Haghighi; B Khosravi; A Bahmanabadi; Kh Davari (طب کار)
Abstract Background: Occupational exposure to styrene can lead to various psychological and somatic complaints including color vision disorder that can occur even in low concentrations. Color vision disease is an early clue for effect of styrene on human, which can be used as an appropriate screening method in workers exposed to styrene. Materials and Methods: Working in waxy foundry is a job with exposure to styrene. This study has been performed to evaluate color vision of workers who work in this factory. When considering inclusion and exclusion criteria, 35 waxy foundry workers and 62 workers unexposed to styrene were assessed. To determine color confusion Index we used Launtony D15 d test to discover yellow-blue color vision disorder. Urinary mandelic acid in end shift of the first workday was measured as biologic exposure monitoring. Results: There was no difference in age between cases and controls (P=0.2). Color confusion index in cases was significantly higher than control group (P=0.017). Urinary mandelic acid of cases was in the range of 1000-1400 mg/l that indicate daily exposure to more than 50 ppm (OSHA PEL) of styrene. There was no significant correlation between uric mandelic acid and color vision disorders (P=0.93). There was no correlation between age and color vision disorders too (CC=-0.01). Conclusion: Exposure to styrene in a concentration above permissible limit can cause color vision disorders.